Development of a Textured Picture Book Equipped with Crosswords as a Media for Learning Biology Sub-Material Epithelial Tissue - Anggraeni, Fima Diah Rovvy; Rassy, Regania Pasca; Sereesuchat, Sopida (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: To test the suitability of textured picture books equipped with crossword puzzles as a learning medium for Biology, epithelial tissue sub-material for class XI semester 1, it was assessed by experts and teachers and reviewed based on the effectiveness of its use. Methodology: This research uses the Research and Development (R&D) method with a 4-D development model. The research samples involved were 18 test students and 16 control students. Qualitative data was obtained from advice from material experts and media experts, quantitative data from the results of assessments carried out by media experts, material experts, teachers and students Main Findings: Based on the assessment of media material experts, it has appropriate criteria (very good) with a percentage of 90.9%, the assessment according to media experts is included in the appropriate criteria (very good) with a percentage of 85.5% and the assessment according to teaching teachers is in the appropriate category (very good) with a percentage of 98.48%. The effectiveness of the media on student grades is in the quite effective category with an average test student score of 6.77 compared to an average control student score of 5.70. The media readability test after use in learning is in the very good category with a percentage of 86.1%. Novelty/Originality of this study: The novelty of this research lies in its innovative approach in presenting learning materials, expanding evaluation methods, and its potential to increase students' understanding and involvement in learning epithelial tissue topics.